Why Mindfulness Is Not Sati: The Genealogy of the Mindfulness Boom - Baatz, Ursula (Buddhist Christian studies, 2026)
The practice of sati, mindfulness, is a fundamental exercise of Buddhism, embedded in and explained by Buddhist philosophical reflection. In just a few decades, a largely unknown Buddhist meditation practice has become a method used by psychotherapists, hospitals, and even the U.S. military. Colonialism and the modernization of Buddhism led to a modernization of Vipassana practice. In this modernized form, mindfulness practice became medicalized and a useful mental tool in an industrial information society. Today, mindfulness practice is a tool for self-optimization, but also a method of healing and strengthening. Both the practice and the theoretical understanding of the practice have changed: it is not about nirvana, but about self-regulation, self-control, and efficiency.